FORMULATION AND EVALUATION OF TOPICAL HERBAL GEL CONTAINING INCLUSION COMPLEX OF CURCUMIN: VANDANA D*, SHWETA PAWAR - VANDANA D; SHWETA PAWAR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The current work was aimed to prepare a topical gel containing curcumin (CUR) for the treatment of microbial infections on skin. Methods: CUR was complexed with the β-cyclodextrin (β-CD) using kneading method in 1:1, 1:2, and 1:3 molar ratios and characterized. The inclusion complex with high aqueous solubility was loaded in the topical gel containing (2% CUR) which was prepared using carbopol, sodium CMC, and guar gum and evaluated for viscosity, spreadability, extrudability, pH, drug content, and in vitro diffusion studies. The in vitro anti-inflammatory activity of the gel was performed by albumin protein denaturation technique, the statistical analysis was done using ANOVA followed Dunnett’s t-test. The antimicrobial activity of CUR was evaluated using standard strains of Candida albicans and Escherichia coli by agar well diffusion method. Results: The complexation of CUR had an increased solubility up to 103.09 times for 1:3 molar ratio with in vitro dissolution 90.64% for 60 min. The optimized formulation F9 had viscosity of 6500.3 cps and 97.5% in vitro drug diffusion for 8 h which follows zero-order release kinetics. In vitro anti-inflammatory activity studied showed that the CUR gel has a good potency for renaturation and was as effective as standard diclofenac with 76.9% inhibition (p=0.0507). CUR showed approx. 3 mm diameter of zone of inhibition against C. albicans and E. coli. Conclusion: A stable topical gel of CUR using β-CD and carbopol was successfully prepared which showed better in vitro diffusion with promising anti-inflammatory and antifungal action.